Dynamics of the attentional blink in preverbal infants - François Leroy; Shruti Naik; Rasa Gulbinaite; Marie Palu; Demian Battaglia; Ghislaine Dehaene-Lambertz (Proceedings of the National Academy of Sciences, 2026)
In the first months postterm, human infants are traditionally viewed as passive to their environment, unable to focus or sustain attention on specific objects. Here, we asked whether 4-mo-old infants could engage their attention strongly enough in a visual task to block the perception of a subsequent interesting stimulus—a phenomenon known as attentional blink, which in adults reflects a serial processing bottleneck for accessing a central workspace. We presented three successive visual events: a central teddy bear (T1) followed by a lateralized face and scrambled face (T2) at varying stimulus onset asynchrony (SOAs: 400, 800, and 1,200 ms), then the same face reappeared after 1,600 ms (T3). We monitored saccades toward the face, pupil size, and electroencephalic (EEG) responses to the flickering background. Our behavioral and EEG results showed that infants missed the lateralized face at the shortest SOA (400 ms). At 800 ms, detection occurred only when the face appeared in the left hemifield, while detection in the right hemifield required 1,200 ms, suggesting a hemispheric asymmetry in face processing. Furthermore, at SOAs where T2 should be visible, a trial-by-trial metric based on event-related variability revealed that the depth of attentional engagement to T1 predicted access to T2, despite identical visual input. These findings support the presence of a global workspace in early infancy, though with slower dynamics.